Kajian Struktural-Semiotik Ian Richard Netton terhadap Q.S. Al-Kahf - Fadlillah, Nilna; Mahfudh, Hasan (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
This paper describes the structural-semiotic perspective of Ian Richard Netton towards the Qur’anic interpretation of Surah al-Kahf. The analysis departs from the theory of “surah as a whole”, means that a surah of the Qur’an is a collection of the interconnected units. Netton does not provide a thorough interpretation of surah al-Kahf, he only focuses on four stories narrated therein. He argues that the stories in surah al-Kahf contain archetypes and theologemes, and the core of this surah is chaos and harmony. He further stated that every chaos will always be followed by harmony which comes from God’s intervention. On the other hand, I also compare Netton’s interpretation with the structural-thematic approach initiated by Muh}ammad al-Ghaz?l? . In contrast to Netton, al-Ghaz?l? concluds that the essence of surah al-Kahf is to establish monotheistic beliefs.